O FINANCIAMENTO DO PROGRAMA NACIONAL DE ASSISTÊNCIA ESTUDANTIL (PNAES) NO INSTITUTO FEDERAL DO ESPÍRITO SANTO (IFES): ENTRE GANHOS, PERDAS E LUTAS - Surdine, Monya Carla da Costa (2020)
This dissertation has the objective of study the financing of student s assistance policy at the Federal Institute of Espírito Santo IFES between 2012 and 2018. It aims to understand, on the context of budget cuts, how the execution of such programs a